Chalcones are potential inhibitors of HIV-1 protease - Ivković, Branka; Turković, Nemanja; Tasić, Milica; Kotur-Stevuljević, Jelena; Vujić, Zorica; Ivković, Aleksandar (Archives of Pharmacy, 2022)
The discovery of HIV and the study of molecular mechanisms crucial for the virus replication cycle have led to the identification of important protein structures - potential targets of drug action in AIDS therapy. One of the most significant discoveries is HIV-1 protease (PR), an enzyme that plays a key role in the HIV replication cycle. This study aimed to test and demonstrate the interactions of newly synthesized chalcones (1,3-diaryl-2-propen-1-one) as well as three commercial drugs (lopinavir, ritonavir and darunavir) in the active site of HIV-1 protease using in sillico methods. and that the results obtained correlate with the results of in vitro tests on the enzyme itself. The twenty structurally similar chalcone derivatives were synthesized and their physico-chemical characterization was performed. Docking calculations were performed using the Autodock Wine program in the 3D structure of the enzime catalytic site (pdb code: 6B36). The inhibition of enzyme activity was monitored by fluorimetric method. The obtained results revealed that all compounds showed anti-HIV-1 protease activity. Compound C1 showed the highest inhibitory activity with an IC50 values of 0.001 µM which is comparable with commercial product Darunavir. The results obtained indicate that the synthesized compounds can be classified as potential anti-HIV-1 protease inhibitors. Further research is focused on testing the ADMET properties of the synthesized compounds as well as the synthesis of their analogues for which in silico tests have shown satisfactory results.